Analyzing Economic Implications of Climate Change in Pakistan; A Legal Frame work Approach - Dr. Bahadar Ali (Journal of Peace, Development and Communication, 2024)
The effects of global warming are coming out with more intensity this time and it is no wonder that the main reason for this is the increasing and unjustified interference of man in the nature. No matter whether it is the movement of stars and galaxies in the vast air space, the attractive scenery of trees, mountains and rivers, the charming and melodious sound of birds, or the order and discipline in the life of different kinds of animals, it says in a very clear and concise way that the Creator of the universe has created all these thing in a very complete and comprehensive in terms of balance and order in a very flawless manner. At the same time, this merciful Lord also directed that do not disturb the balance of the nature. But what to say about the human beings, his greediness by nature, he messed up the natural arrangement of this beautiful and balanced mother earth in such a way that countless social, economic and environmental issues started appearing on daily basis.